2022
DOI: 10.1007/s10943-022-01573-x
|View full text |Cite
|
Sign up to set email alerts
|

Global Research Trends of Health-Related Publications on Ramadan Fasting from 1999 to 2021: A Bibliometric Analysis

Abstract: Ramadan fasting is one of the five pillars of Islam. The current study aims to examine, analyze, and identify trends of health-related publications on Ramadan fasting. In total, 1468 documents retrieved from Scopus were analyzed. The mean number of authors per document was 3.7, with an average of 13.3 citations per document. The UK ranked first (12.3%, n = 181) regarding the number of documents, followed by Iran (10.4%, n = 153) and then Saudi Arabia (9.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The study revealed a strong and significant correlation ( p < 0.001; r = 0.958) between the two sets of results, indicating the high level of validity of the research strategy. Notably, Sweileh et al previously employed this validation approach [ 73 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study revealed a strong and significant correlation ( p < 0.001; r = 0.958) between the two sets of results, indicating the high level of validity of the research strategy. Notably, Sweileh et al previously employed this validation approach [ 73 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study's findings revealed a significant and strong correlation ( p = 0.001; r = 0.955) between the two sets of results, indicating the research strategy's high level of validity. Notably, Sweileh et al previously used this validation approach [ 21 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This test found a strong correlation ( r = 0.960) and a significant result ( P = 0.001), showing that the search query was precise. This validation method has already been employed in bibliometric studies[ 46 - 48 ]. The rigorous approach and cooperation of two bibliometric specialists enhanced the findings’ trustworthiness, and the correlation test gave additional support.…”
Section: Methodsmentioning
confidence: 99%